(untitled) (Medicine Today, 2025)
Introduction with objective: Urolithiasis, a prevalent urologic condition affecting 10-15% of the population, poses significant challenges, particularly in impoverished nations where complications such as urosepsis and renal failure contribute to elevated morbidity rates. The surgical management of stone disease has evolved from traditional open procedures to include non-invasive and minimally invasive techniques, driven by factors such as stone location and size. Percutaneous nephrolithotomy (PCNL) introduced in 1955, revolutionized the approach to kidney stones, and its popularity has grown, especially for larger kidney stones and upper ureteric stones. The aim of this study was to observe and assess the outcomes of percutaneous nephrolithotomy in managing large upper ureteric stones. Materials and Methods: This prospective observational study was carried out among 35 patients attending at the department of Urology at Sir Salimullah Medical College Mitford Hospital, Dhaka for the treatment of upper ureteric stone within the defined period from January 2019 to December 2020. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: The clinical features of patients who underwent PCNL were analyzed, revealing a mean stone size of 20.05 mm, an operative time of 90.17 minutes, and a postoperative hospital stay of 1.80 days. The distribution of stones on the right and left ureters was 51.40% and 48.60%, respectively, with a stone clearance rate of 97.1% and a 2.9% incidence of residual stones. The study further assessed postoperative complications, reporting per-operative complications in 28.6% of cases, including bleeding, pleural and renal pelvis injuries, and post-operative complications in 31.4%, such as fever, blood transfusion, and urinary leakage. Conclusion: Mean operative time, hospital stay was less. Comparative analysis revealed PCNL as a less morbid procedure, aligning with its established efficacy for stone clearance. The study contributes valuable insights into the clinical outcomes and complications associated with PCNL, offering considerations for its application in managing large upper ureteric stones. Medicine Today 2025, Vol.37 (2): 233-236